2003
DOI: 10.1107/s0108768102021341
|View full text |Cite
|
Sign up to set email alerts
|

The modulated structure of Ba0.39Sr0.61Nb2O6. I. Harmonic solution

Abstract: The structure of a crystal of Sr0.61Ba0.39Nb2O6 has been solved and refined as an incommensurate structure in five-dimensional superspace. The structure is tetragonal, superspace group P4bm(\,pp1/2,p - p1/2), unit-cell parameters a = 12.4566 (9), c = 7.8698 (6) Å, modulation vectors q 1 = 0.3075 (6) (a* + b*), q 2 = 0.3075 (6) (a* − b*). The data collection was performed on a KUMA-CCD diffractometer and allowed the integration of weak first-order satellite reflections. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 22 publications
10
86
0
1
Order By: Relevance
“…As Woike et al observed with a Ba 0.39 Sr 0.61 Nb 2 O 6 single crystal [23], the oxygen ions in the barium and lanthanum layer display strong anisotropic displacements, with a rounded thermal ellipsoid for O1, and lengthened ones for O5. The oxygens ions located in the iron and niobium layer exhibit thermal ellipsoids, which are pointing along the Oz direction (Fig.…”
Section: Structural Study Of a Lafno Single Crystalmentioning
confidence: 72%
See 2 more Smart Citations
“…As Woike et al observed with a Ba 0.39 Sr 0.61 Nb 2 O 6 single crystal [23], the oxygen ions in the barium and lanthanum layer display strong anisotropic displacements, with a rounded thermal ellipsoid for O1, and lengthened ones for O5. The oxygens ions located in the iron and niobium layer exhibit thermal ellipsoids, which are pointing along the Oz direction (Fig.…”
Section: Structural Study Of a Lafno Single Crystalmentioning
confidence: 72%
“…This may be the sign that a modulation takes place in the LaFNO polyhedral framework, as it is the case for Ba 0.39 Sr 0.61 Nb 2 O 6 and similar TTB systems. This may be related to the modulation of the structure observed in some crystals as mentioned above, which required a double unit cell parameter along c direction (a structural model close to the suggested one by Woike et al [23]). The crystal structure of LaFNO we present here will certainly be used as a basis structure for a detailed description of modulated LnFNO crystals with the 3Dþ n approach.…”
Section: Structural Study Of a Lafno Single Crystalmentioning
confidence: 85%
See 1 more Smart Citation
“…They are tetragonal, with space group P4bm for the ferroelectric phase [18,19]. Since the Curie temperatures are located above 320 K [1], and the present spectral measurements have been carried out at RT or low temperature, all results are relative to the ferroelectric phase.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, the incommensurate structure of SBN was solved and refined as a five dimensional (5D) modulated structure in the superspace formalism. [49] In 2012, Graetsch et al [50][51] [52][53][54][55] demonstrated that both Bi-and La-based compounds exhibit relaxor behavior, whereas Nd-, Sm-, and Gd-based analogs are classical ferroelectrics. In Ba 2 RENb 3 Ti 2 O 15 compounds, deviations from the ideal TTB symmetry caused by an incommensurate modulation was associated with relaxor behavior, whereas a commensurate modulation was observed for phases exhibiting ferroelectric behavior.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%